Pengaruh Penggunaan Artificial Intelligence (AI) dan Media Quizizz Terhadap Minat Belajar Mahasiswa pada Mata Kuliah Teknologi Digital Pendidikan - Julia Risky Handayani; Marsofiyati Marsofiyati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research is motivated by the importance of the role of technology in education, especially the use of artificial intelligence (AI) and interactive learning tools such as Quizizz to increase students' interest in learning. The purpose of this study is to analyze the impact of the use of artificial intelligence and Quizizz on students' interest in the Digital Educational Technology course. The research method used is a quantitative approach using a survey method by distributing questionnaires to students of the Jakarta State University Office Administration Training Program in 2022 as the population in this study, with a sample of 50 respondents combined between class A and class B, and analyzed with the help of IBM SPSS Statistic 25 to obtain test results. The results of the study show that the use of AI provides a more personal and effective learning experience, while the Quizizz media creates an interesting learning environment through gamification elements. The combination of these two factors has been shown to have a significant positive impact on increasing students' interest in learning, as evidenced by the high level of student engagement and motivation in the learning process. The findings of this study provide insight for educators to develop innovative technology-based teaching strategies and also encourage educational institutions to use modern technology to improve the quality of education in the digital era.